2011
DOI: 10.5539/ijc.v3n2p180
|View full text |Cite
|
Sign up to set email alerts
|

Preparation of Low Molecular Weight Chitosan by Complex Enzymes Hydrolysis

Abstract: Through the determination of viscosity average molecular weight, enzyme activity, hydrolysis ratio and reducing sugar concentration, the optimal technological conditions of complex enzymes composed of commercial α-amylase, cellulase and pectinase were investigated. Results indicated that complex enzymes could result in low molecular weight chitosan ranged from 1000 to 4000 after enzymatic degradation for 2 h under the condition of zymolyte ratio 1:5(m/m), pH 5.3 and temperature 56℃, and the structure of those … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
13
0
1

Year Published

2014
2014
2022
2022

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 26 publications
(14 citation statements)
references
References 6 publications
0
13
0
1
Order By: Relevance
“…The carbohydrate content of chitosan and each oligochitosan fraction was measured spectrophotometerically by the 3,5-dinitrosalicylic acid (DNS) method [77]. The DNS reagent contained a 1:1:1:1 volumetric mixture of 3,5-dinitrosalicylic acid (1%), Rochelle salt (40%), phenol (0.2%), and potassium bisulfate (0.5%), all dissolved in sodium hydroxide (1.5%).…”
Section: Methodsmentioning
confidence: 99%
“…The carbohydrate content of chitosan and each oligochitosan fraction was measured spectrophotometerically by the 3,5-dinitrosalicylic acid (DNS) method [77]. The DNS reagent contained a 1:1:1:1 volumetric mixture of 3,5-dinitrosalicylic acid (1%), Rochelle salt (40%), phenol (0.2%), and potassium bisulfate (0.5%), all dissolved in sodium hydroxide (1.5%).…”
Section: Methodsmentioning
confidence: 99%
“…Enzymatic hydrolysis leads to chitosan degradation and results in lower molecular weight. Xie (2011) observed that complex enzymes composed of commercial cellulose, pectinase and α-amylase degrade the large molecular chain of chitosan, and as a consequence, molecular weight lowered from 1,000,000 to 100,000. According to Tatro et al (2003), lower thermal stability is caused by decreasing of molecular weight.…”
Section: Antibacterial Activitymentioning
confidence: 99%
“…Greater intensity is observed in the spectral signals of the QsD because the functional groups vibrate with greater freedom of movement because the steric hindrance of the polymer chain decreases. e increase in the intensity of the signal at 3379 cm −1 is due to a greater number of OH groups, while the intensity of the signal at 3260 cm −1 is associated with the greater number of NAcGlc units due to the increase of the AD [27]. e conservation of the signals of absorption of the glycoside bond and the pyranosic ring con rms that the mechanism of action of the enzyme complex is selective at the site of the β (1-4) glycoside bond.…”
Section: Ftir Analysismentioning
confidence: 94%
“…® . At concentrations higher than 1 mg•mL −1 of the enzyme system, degradation is maximal, and up to a limit value of 2.75 × 10 −3 mg•mL −1 , the synergistic e ect of the enzyme system can be considered constant [27]; after this value, the concentration of reducing sugars is constant (Figure 3). A substrate concentration of 1 : 10 was maintained.…”
Section: Optimal Concentration Of Celuzyme Xbmentioning
confidence: 99%